(untitled) (El Taco en la Brea, 2019)
The articule aims to think some aspects of the literature of the southamerican writers Felisberto Hernández, Mario Levrero and Antonio Di Benedetto, taking as corpus small texts and fragments of each, posing the questions on the animal figuration they create to think about the elusive act of writing. It pretends to understand if something like an «animal writing» is possible. This attempt gives capital importance to some consideration about time and to the author-work relation, as well as it takes regards from Derrida´s animality and Deleuze−Guattari vitalist philosophy.